Influence of Maternal Fish Oil Supplementation on the Risk of Asthma or Wheeze in Children: A Meta-Analysis of Randomized Controlled Trials - Wu, Shaojing; Li, Changhong (Frontiers in Pediatrics, 2022)
Background: Previous studies evaluating the influences of maternal fish oil supplementation on the risk of asthma or wheeze in children showed inconsistent results. We performed a meta-analysis or randomized controlled trials (RCTs) to systematically evaluate the efficacy of maternal fish oil supplementation for asthma or wheeze. Methods: Relevant RCTs were obtained by search of PubMed, Embase, and Cochrane’s Library databases. A random-effects model incorporating the potential publication bias was used to pool the results. Results: Ten RCTs with 3676 infants were included. Compared to control, maternal supplementation with fish oil was not associated with a reduced risk of asthma or wheeze (odds ratio [OR]: 0.91, 95% confidence interval [CI]: 0.72 to 1.14, P = 0.40) with mild heterogeneity (I2 = 28%). Subgroup analyses showed that maternal fish oil supplementation significantly reduced the risk of asthma (OR: 0.56. 95% CI: 0.35 to 0.91, P = 0.02; I2 =0%), but not the risk of wheeze (OR: 1.12, 95% CI: 0.90 to 1.41, P = 0.32; I2 =0%). In addition, maternal fish oil supplementation was associated with reduced risk of asthma or wheeze in high-dose studies (≥ 1200 mg/d, OR: 0.65, 95% CI: 0.48 to 0.87, P = 0.003; I2 =0%), but not in low-dose studies (< 1200 mg/d, OR: 1.10, 95% CI: 0.88 to 1.38, P = 0.39; I2 =0%, P for subgroup difference = 0.005). Study characteristics such as the risk of the infants, timing of supplementation, and follow-up duration did not significantly affect the results. Conclusions: Maternal fish oil supplementation may reduce the risk of clinically diagnosed asthma in children, particularly with high-dose fish oil.